Effect of Electromagnetic Fields from Mobile Phones on the Hearing System: A Narrative Review - Azadeh Borna; Mehri Maleki (Shahid Beheshti University of Medical Sciences, 2021)
Background and Aims: Mobile phone use has increased in recent years and there is more than 1.6 billion users worldwide. This has increased speculations about the potential dangers of high-frequency Electromagnetic Fields (EMF) on health. Mobile phones receive and transmit microwave radiation in the frequency range of 800-2000 MHz, and due to the proximity of mobile phones to the head during use, the hearing system and brain are more exposed to radiation compared to other parts of the body. The present study aims to review the studies conducted on examining the effect of EMF from mobile phones on the hearing system. Methods: In this narrative review study, the search was conducted in Google Scholar, PubMed, and Web of Science databases on the related studies. Results: The studies investigating the short-term effects of EMF on the health of auditory system did not report significant effects, but most of those conducted on its long-term effects showed significant effects. Conclusion: Further studies are needed to determine how long after the use of mobile phones the effects can be measured so that the necessary measures can be taken to protect the health of the hearing system.